Dielectric measurement of Pulverized Coriander (Coriandrum sativum Linn.) at microwave frequency. - Karhale, G A; Kalamse, G M (Current Botany, 2012)
The moisture content, conductivity, nutritional quality, dielectric heating effect on germination and growth of agricultural products, are the important with respect to quality maintenance. To understand the actual process at molecular level the investigation on dipolar behavior of coriander (Coriandrum Sativum Linn.) in the form of powder, at microwave frequency 9.85 GHz are carried out for different grain sizes and at different temperatures. The effect of packing density on dielectric parameters, relaxation time, and conductivity of coriander are reported.Experimental results of different relative packing fraction (ï¤r) are further used to obtain transformation to 100% solid bulk, using correlation equations of Landau-Lifshitz-Looyenga and Bottcher. It is found that, there was fair agreement between experimental values and theoretical values. The result shows cohesion in the particles of Coriander powder under investigation.